Effectiveness of Interventions on Improving Balance in Children and Adolescents With Hearing Impairment: A Systematic Review - Zhou, Yan; Qi, Jing (Frontiers in Physiology, 2022)
Although children and adolescents with hearing impairment are at risks of falls from balance problems, reliable information on effects of interventions are scare. Therefore, the purpose of this review is to systematically summarize studies on the evidence of interventions to improve balance ability in children and adolescents with hearing impairment. A systematic literature search was conducted on five major electronic databases. Studies were included if: 1) interventions or trials focusing on improving balance in children and adolescents with hearing impairment; 2) research targeting children with hearing impairment (samples with a mean age below 18 years); 3) studies were published in English peer-reviewed journals due to language barriers and resource limitations; and 4) study designs were randomized controlled trial or quasi-experiment. A nine-item tool adapted from the Consolidated Standards of Reporting Trials Statement was used to assess the quality of the studies. Through the search strategy, 373 articles were identified, and 15 studies published between 1981 and 2021 met the inclusion criteria. Most of the studies reviewed were categorized as medium or low quality, and only three were identified as high quality. Exercise interventions were adopted in 80% of the included studies, whereas studies that employed music + vibration, motor, and game as the intervention modalities accounted for the remaining 20.0%. The results of this review showed that the included trials with exercise interventions had a positive influence on the balance among children and adolescents with hearing impairment (the post-intervention scores were significantly higher than the pre-intervention or the control group scores). In addition, the interventions with duration of 8–16 weeks were more effective than those with less than 8 weeks. However, due to most of the reviewed studies were of low methodological quality, the trials results analyzed by this systematic review should be interpreted with caution. Further investigations of high-quality studies are therefore needed to prove the effectiveness of interventions on improving balance performance in children and adolescents with hearing impairment. Systematic Review Registration: [https://www.crd.york.ac.uk/PROSPERO/], PROSPERO [308803].